The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jawr.12221
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Water and Sediment Quality and Hydrologic Processes on Mussels in the Clinch River

Abstract: Segments of the Clinch River in Virginia have experienced declining freshwater mussel populations during the past 40 years, while other segments of the river continue to support some of the richest mussel communities in the country. The close proximity of these contrasting reaches provides a study area where differences in climate, hydrology, and historic mussel distribution are minimal. The USGS conducted a study between 2009 and 2011 to evaluate possible causes of the mussel declines. Evaluation of mussel ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(77 citation statements)
references
References 49 publications
4
72
1
Order By: Relevance
“…Prior research has found spatial and temporal associations of elevated TDS concentrations with freshwater mussel declines in the Clinch River in Virginia (Johnson et al, 2014;Price et al, 2014), suggesting that elevated major ions may be causing toxicity in the Clinch River. This idea also applies to the Powell River, where TDS concentrations are substantially higher in the upper reaches of the river and mussel populations have experienced long-term declines at monitoring locations downstream of these high TDS reaches (Ahlstedt et al, 2005;Johnson et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prior research has found spatial and temporal associations of elevated TDS concentrations with freshwater mussel declines in the Clinch River in Virginia (Johnson et al, 2014;Price et al, 2014), suggesting that elevated major ions may be causing toxicity in the Clinch River. This idea also applies to the Powell River, where TDS concentrations are substantially higher in the upper reaches of the river and mussel populations have experienced long-term declines at monitoring locations downstream of these high TDS reaches (Ahlstedt et al, 2005;Johnson et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Independent biological monitoring, initiated in 1979, has documented significant declines of freshwater mussel richness and density in sections of Clinch River and throughout the Powell River (Ahlstedt et al, 2005;Johnson et al, 2012;Jones et al, 2014). Recent research has found a spatial association between elevated TDS concentrations and declining freshwater mussel populations in the Clinch River; reaches of the river experiencing the greatest declines in mussel richness and density have elevated concentrations of major ions relative to other reaches of the river where mussel populations are stable (Johnson et al, 2014). In upper segments of the Powell River, TDS concentrations are greater than at any location in the Clinch River (Price et al, 2011) and severe declines of mussel richness and density have been observed in surveyed reaches of the Powell River located downstream of the high TDS reaches (Ahlstedt et al, 2005;Johnson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Given the spatial extent of surface mining in the upper Powell watershed, it is not surprising that these constituents also are elevated in the Powell River itself. Lindberg et al (2011) also found elevated concentrations of mining-origin constituents in a non-headwater stream influenced by mining, as did Johnson et al (2014) in the Clinch River of southwestern Virginia and eastern Tennessee. Johnson et al (2014) also observed diminishing concentrations of mining-influenced constituents and SC moving downstream from mining influence in the Clinch River of Virginia and Tennessee, which they attributed to dilution caused by influxes of waters from non-mined tributaries.…”
Section: Water Qualitymentioning
confidence: 88%
“…Freshwater mussels have experienced high rates of imperilment globally (Williams et al, 1993;Lydeard et al, 2004;Strayer et al, 2004;IUCN, 2015). Mussel declines have occurred in several North American rivers affected by watershed mining (Warren and Haag, 2005;Angelo et al, 2007;Johnson et al, 2014) as well as in the Powell River (Ahlstedt et al, 2015). There is interest in the region to identify specific toxicants that are responsible for the mussel declines that have been observed in streams draining the Appalachian coalfield (Warren and Haag, 2005;Jones et al, 2014) and to determine if such toxicants originate from mining.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation